OP17 The stability of treatment preferences among patients with advanced cancer. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Jabbarian, L; Maciejewski, R; Maciejewski, P; Rietjens, J; Korfage, I; van der Heide, A; van Delden, J; Prigerson, H
Abstract : Background: Stability of patients' treatment preferences has important implications for advance care planning, among which its timing. We therefore examined the stability of preferences and its predictors of patients with advanced cancer. Methods: In this cohort, 104 patients with metastatic cancer and an oncologist estimated life-expectancy of ≤ six months participated in interviews following clinical visits in which patients' recent scan results were discussed. Interviews were repeated in three monthly follow-ups. At baseline, patients' age, education, sex, race, marital status, insurance status, and type of cancer were documented. At each assessment, patients reported their treatment preferences (i.e. trade-offs of life-prolonging versus comfort care), quality of life, and illness understanding. Results: At baseline (n=104), 55 (53%) patients preferred life-prolonging care, 49 (47%) preferred comfort care. Patients were followed for one (n=104), two (n=74), or three months (n=44). Between baseline and month I, 84 patients (81%) had stable treatment preferences. During follow-up, preferences of 71 patients (68%) remained stable (equally divided between a consistent preference for life-prolonging and comfort care). Treatment preferences of 33 (32%) patients changed at least once during follow-up. Patients' preferences at baseline strongly predicted preferences at month I (OR=17.8; CI=6.7–47.3; p<.001). Patient characteristics, quality of life, and illness understanding at baseline were not significantly associated with stability of preferences at month I. Conclusion: Two-thirds of patients with advanced cancer had stable preferences regarding life-prolonging versus comfort care. Changes of preferences were often unpredictable. Our findings suggest potential benefits of ongoing communication about preferences, including advance care planning.